Comparison of low-profile plate-screw and Kirschner-wire osteosynthesis outcomes in extra-articular unstable proximal phalangeal fractures - Kose, Ahmet; Sencan, Ayse; Topal, Murat; Engi̇n, Muhammed Çağatay; Baran, Tuncay; Di̇nçer, Recep (Springer Science and Business Media LLC, 2018)
We aimed to present the radiological and clinical results of Kirschner-wire (K-wire) fixation and low-profile plate-screw fixation applied to unstable proximal phalangeal fractures without extension to the joint.Clinical and radiological data of 22 patients who underwent fixation with open reduction and low-profile 1.5-mm titanium mini plate and unlocked screws and 18 patients who underwent fixation with K-wire due to closed, unstable extra-articular proximal phalangeal fractures were retrospectively examined. All evaluation and statistical analyses were based on sixth postoperative month evaluation parameters. Active and passive metacarpophalangeal joint and interphalangeal joint range of motions, total joint range of motion, measurement of grip strength for fractured and healthy hands, visual analog scoring, disabilities of the arm, shoulder, and hand scores, measurement of distance between the pulpa and palmar curve in the operated finger, Belsky score, reoperation, and complications were evaluated.Radiological union was achieved in all patients in a mean duration of 4.2 (3-6) weeks. When the functional results of the patients were evaluated, the mean active metacarpophalangeal joint flexion was 87.3° (75°-90°), mean proximal interphalangeal joint flexion was 94.3° (65°-100°), mean distal interphalangeal joint flexion was 77.6° (75°-80°), and mean total range of motion was 259° (210°-270°). The grip strength of the fractured hand was 52.7 (40-58) kgW, whereas that of the healthy hand was 54.4 (42-60) kgW. The mean value of visual analog score was 0.8 (0-2), mean score for disabilities of the arm, shoulder, and hand was 7 (2-27), and mean distance between the finger pulpa and finger curve was 3 (0-8) mm.Plate-screw osteosynthesis in the extra-articular, unstable fractures of the proximal phalanx, which is "small" compared with the body but has a "major function" for the hand and upper extremity, allows for rigid fixation, short immobilization, and early motion in spiral/oblique-fragmented fractures. K-wire fixation, an alternative treatment modality, applied to selected fracture patterns with appropriate indications can achieve good-excellent results radiologically and functionally.
Keywords: Adult; Male; Reoperation; Hand Strength; Bone Screws; Middle Aged; Finger Phalanges; Fracture Fixation, Internal; Fractures, Bone; Open Fracture Reduction; Young Adult; Treatment Outcome; Finger Joint; Humans; Female; Range of Motion, Articular; Bone Plates; Aged; Bone Wires; Retrospective Studies